EuroFlow Standardized Approach to Diagnostic Immunopheneotyping of Severe PID in Newborns and Young Children - Kalina, Tomas; Bakardjieva, Marina; Blom, Maartje; Perez-Andres, Martin; Barendregt, Barbara; Kanderová, Veronika; Bonroy, Carolien; Philippé, Jan; Blanco, Elena; Pico-Knijnenburg, Ingrid; Paping, Jitse H. M. P.; Wolska-Kuśnierz, Beata; et al. (Frontiers in Immunology, 2020)
The EuroFlow PID consortium developed a set of flow cytometry tests for evaluation of patients with suspicion of primary immunodeficiency (PID). In this technical report we evaluate the performance of the SCID-RTE tube that explores the presence of recent thymic emigrants (RTE) together with T-cell activation status and maturation stages and discuss its applicability in the context of the broader EuroFlow PID flow cytometry testing algorithm for diagnostic orientation of PID of the lymphoid system. We have analyzed peripheral blood cells of 26 patients diagnosed between birth and two years of age with a genetically defined primary immunodeficiency disorder: 15 severe combined immunodeficiency (SCID) patients had disease-causing mutations in RAG1 or RAG2 (n=4, two of them presented with Omenn syndrome), IL2RG (n=4, one of them with confirmed maternal engraftment), NHEJ1 (n=1), CD3E (n=1), ADA (n=1), JAK3 (n=3, two of them with maternal engraftment) and DCLRE1C (n=1) and 11 other PID patients had diverse molecular defects (ZAP70 (n=1), WAS (n=2), PNP (n=1), FOXP3 (n=1), del22q11.2 (DiGeorge n=4), CDC42 (n=1) and FAS (n=1)). In addition, 44 healthy controls in the same age group were analyzed using the SCID-RTE tube in four EuroFlow laboratories using a standardized 8-color approach. RTE were defined as CD62L+CD45RO-HLA-DR-CD31+ and the activation status was assessed by the expression of HLA-DR+. Naïve CD8+ T-lymphocytes and naïve CD4+ T-lymphocytes were defined as CD62L+CD45RO-HLA-DR-. With the SCID-RTE tube, we identified patients with PID by low levels or absence of RTE in comparison to controls as well as low levels of naïve CD4+ and naïve CD8+ lymphocytes. These parameters yielded 100% sensitivity for SCID. All SCID patients had absence of RTE, including the patients with confirmed maternal engraftment or oligoclonally expanded T-cells characteristic for Omenn syndrome. Another dominant finding was the increased numbers of activated CD4+HLA-DR+ and CD8+HLA-DR+ lymphocytes. Therefore, the EuroFlow SCID-RTE tube together with the previously published PIDOT tube form a sensitive and complete cytometric diagnostic test suitable for patients suspected of severe PID (SCID or CID) as well as for children identified via newborn screening programs for SCID with low or absent T-cell receptor excision circles (TRECs).